Design, development and optimization of new high performance thin‐layer chromatography method for quantitation of Retapamulin in pharmaceutical formulation: Application of design of experiment. Issue 4 (20th January 2020) - Patel, Rashmin; Patel, Nishant; Patel, Mrunali
Abstract: The objective of the present study was to design, develop and optimize Design of Experiments supported high performance thin‐layer chromatography method for quantitative estimation of Retapamulin in marketed cream and microemulsion formulations. Design of Experiments help to identify and understand the effect of important factors on response with minimum experimental run in developing robust method. To optimize chromatographic conditions and to study their effects on separation of Retapamulin, Box–Behnken experimental design was selected. Experimental conditions with desirability 1 were selected which gave the optimal composition of methanol in mobile phase along with ethyl acetate: ammonia, development distance of 70 millimeter and chamber saturation time of 22 minutes. Retapamulin was well separated with retardation factor value 0.60 from excipients of marketed cream formulation on high performance thin‐layer chromatography plate using optimized chromatographic conditions. The optimized method was validated and statistical analysis proved that the method is specific, sensitive, accurate and precise. A new high performance thin‐layer chromatography has been successfully designed, developed, optimized and validated for quantification of Retapamulin in cream formulation using Box–Behnken design. The proposed high performance thin‐layer chromatography method is easy, convenient, reliable and accurate for the routine analysis of Retapamulin in marketed cream and microemulsion formulations.